Vector Bond Graph Method for the Computer Modeling and Kineto-static Analysis of a Single-DOF Double Crank Six-bar Press Mechanism - Wang Zhongshuang; Yin Jiuzheng; Gao Mengqi (Jixie chuandong, 2020)
For the problem of computer modeling and kineto-static analysis for a single-DOF double crank six-bar press mechanism， the corresponding vector bond graph method is proposed. From the mechanism structure and composition principle， the corresponding vector bond graph model is built. By the effective method， all the energy storage elements of the mechanism vector bond graph posses integral causality. As a result， the algebraic difficulty of computer modeling for mechanism kineto-static analysis is solved. By the corresponding algorithm， the computer modeling and kineto-static analysis of a single-DOF double crank six-bar press mechanism is realized， the effect of the pulse working resistance on mechanism driving moment and joint constraint force is analyzed， and the reliability and validity of the procedure proposed is illustrated.